Research on the value of ultrasound guided core needle biopsy in breast cancer diagnosis - Tuu, Nguyen; Toan, Le Minh; Quan, Nguyen Phuoc Bao; Can, Nguyen Dinh; Bang, Nguyen Van; Thao, Huynh Thi Minh; Tam, Ho Dac Phuong; Thang, Ton That (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2025)
.